1979
DOI: 10.1063/1.437622
|View full text |Cite
|
Sign up to set email alerts
|

Solute orientation behavior in nematic solutions: Trichlorobenzene in MBBA

Abstract: 1,3,5-trichlorobenzene is used as a probe to study the order parameters in MBBA. The NMR spectrum of 1,3,5-trichlorobenzene in MBBA is reported. (AIP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…An early approach to calculating the molecular alignment of solute molecules suggested that the minimum moment of inertia (MOI) axis gave a good description of the principal molecular axis for a range of substituted benzenes, including some of low symmetry, in a nematic host. 15 Subsequent NMR studies have applied this approach to analyse a range of different solutes with varying degrees of success: some reports have noted slight deviations of the principal molecular axis from the minimum MOI axis that were attributable to steric effects, 16,17 whereas others have suggested that the approach does not apply to some systems, 18 and that shape-based approaches are more appropriate to cover a wide range of solute molecules. 19,20 However, in the limiting case of a rod-like molecule of high symmetry, the minimum MOI axis will match the principal symmetry axis, and hence its principal molecular axis.…”
Section: Introductionmentioning
confidence: 99%
“…An early approach to calculating the molecular alignment of solute molecules suggested that the minimum moment of inertia (MOI) axis gave a good description of the principal molecular axis for a range of substituted benzenes, including some of low symmetry, in a nematic host. 15 Subsequent NMR studies have applied this approach to analyse a range of different solutes with varying degrees of success: some reports have noted slight deviations of the principal molecular axis from the minimum MOI axis that were attributable to steric effects, 16,17 whereas others have suggested that the approach does not apply to some systems, 18 and that shape-based approaches are more appropriate to cover a wide range of solute molecules. 19,20 However, in the limiting case of a rod-like molecule of high symmetry, the minimum MOI axis will match the principal symmetry axis, and hence its principal molecular axis.…”
Section: Introductionmentioning
confidence: 99%